PROFESSIONALISM: AS A SOLUTION TO CONTEMPORARY PROBLEMS IN FUNCTIONAL MATHEMATICS EDUCATION IN NIGERIA - F.O, OJO A.A, EGBON; C.A., ALADESAYE (IJRDO -JOURNAL OF MATHEMATICS, 2016)
This paper stresses on categories of mathematics Teachers and controversy over professional recognition as regards challenges that confront educational professionals most especially functional issues in Nigeria. Stakeholders of today and tomorrow should be prepared to effect changes and innovation and promote the image of mathematics teacher education in Nigeria through professionalism. Standard for practice vis-a-vis the quality and effectiveness of teachers who have competencies through specially designed programmes for solving specific task. The characteristics of a professional, the code of conduct, control of entry and the recognition of the occupation of teacher is being zero into. Some recommendations were made. Professional association like MAN, NMS should provide new teachers and their mentors with external peer support through meetings, conference, publication and other resources. The association should ensure that mathematics teachers education programme should be built around professional standards provided by accrediting agencies, department of education and other educational entities. Hence educational authorities should reach a consensus such that mathematics education must be transformed to meet the needs of an emerging information technology and service –based society.